Functional Analysis of ‘Teacher English’ Used by Content-subject Teachers: A Case Study - Poudel, Kamal Kumar (Journal of NELTA, 2020)
Providing ‘quality education’ through English is a challenge for the prestige and survival of private schools in Nepal. In this background, a private school in Kathamandu, having realized that its content-subject teachers had to be better-equipped with the classroom-based English language proficiency, offered the researcher to conduct a short-term teacher training program on ‘teacher English’ for them. With a view to preparing for the short-term ‘training course’, the researcher undertook to investigate the current status of the affairs. The present article reports on an observational case study, informed by the grounded theory methods, on the usual classroom teachings performed by nine content-subject teachers at the school. The major functions of the ‘teacher English’ served as the basis for the thematic analysis of the data. As the findings of the study, fifteen classroom functions of the ‘teacher English’, were identified, namely, greeting, introducing the lesson and lesson activities, defining, checking understanding, asking, instructing, giving feedback, encouraging, controlling, personalizing/labelling, asking for and giving permission, cautioning, thanking, attracting attention and closing the lesson. Finally, the study recommended that the forthcoming teacher training should target at these functions of teaching English with a view to building on and improving their classroom English.